Rapid response in relapsed follicular lymphoma with massive chylous ascites to anti-CD19 CAR T therapy using Piggy Bac: A case report - Zhang, Yan; Lin, Zhicai; Zhang, Faliang; Chen, Xiuxiu; Yang, Yaping; Fu, Xin; Li, Zhong; Sun, Yan; Qian, Qijun (Frontiers in Immunology, 2022)
CD19-directed chimeric antigen receptor (CAR) T cell therapy has been shown to achieve a considerably durable response in patients with refractory or relapsed B cell non-Hodgkin lymphomas, as seen from the results of Zuma-1, Zuma-5, and other clinical trials. Most of these CARs were generated by lentivirus or reverse adenovirus. It is rare to see CARs using non-viral vectors, such as Piggy Bac (pb), in treating lymphoma patients with active diseases. Generally, patients with a high tumor burden tend to have a higher rate of severe cytokine release syndrome (CRS) or neurological events as reported in the literature. Patients with symptomatic pleural effusions are excluded from the Zuma-1 trial because of the risk of severe CRS. We report here that a patient with relapsed follicular lymphoma with bulky disease and massive chylous ascites failed several lines of chemotherapy. After infusion of the CD19-directed pbCAR-T cells at 6 × 106 cells/kg, the patient had a rapid response and achieved a nearly complete metabolic remission on day 28. There was only grade 1 CRS, and no neurotoxicity occurred. The CAR-T cells reached a peak level on day 14 and spread into the ascites and expanded for 3 months. This might be the first case reported for pbCAR-T cells to treat relapsed follicular lymphoma directly. The long-term efficacy will be observed, and more patients be tested in the future. Clinical Trial Registration https://ClinicalTrials.gov, identifier NCT05472610.